Location update schemes for mobile agents - Sushil, Rama; Bhargava, Rama; Garg, Kumkum (INFOCOMP Journal of Computer Science, 2008)
For mobile agents roaming in a network, location management strategies still represent a current research issue, for contacting and communicating with these agents. The cost of a location management strategy mainly depends on the cost of location search and update. In order to save this cost, mobile agents should not update their location every time they change the host. This paper discusses three strategies in which mobile agents make decisions about when and where to update their location: the time-based strategy, the movements-based strategy and the strategy based on counting the migrations host wise and birth-region wise. We propose the birth-region wise movement based location update strategy, named Broadcasting with Search by Path Chase (BSPC), which is an extension of SPC (Search by Path Chase). We have analyzed and compared the performance of both SPC and BSPC and found that BSPC costs less than SPC for low call to mobility ratio (CMR).